Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine which of the given equations are quadratic equations, we need to analyze their forms and verify if they meet the criteria for being quadratic equations. A quadratic equation is a polynomial equation of the second degree, which means it must be of the form [tex]\(ax^2 + bx + c = 0\)[/tex], where [tex]\(a \neq 0\)[/tex].
Let's look at each option one by one.
### Option (a): [tex]\(x^3 - x = x^2 + 2\)[/tex]
To begin, we'll rearrange the terms to bring all terms to one side of the equation.
[tex]\[ x^3 - x - x^2 - 2 = 0 \][/tex]
Next, we combine like terms.
[tex]\[ x^3 - x^2 - x - 2 = 0 \][/tex]
The resulting equation is [tex]\(x^3 - x^2 - x - 2 = 0\)[/tex]. This equation is a polynomial equation of degree 3 (cubic), as the highest power of [tex]\(x\)[/tex] is 3. A quadratic equation must have a highest power of [tex]\(x\)[/tex] equal to 2.
Therefore, [tex]\(x^3 - x = x^2 + 2\)[/tex] is not a quadratic equation.
### Option (b): [tex]\(\sqrt{x + 4} = x + 1\)[/tex]
First, let's eliminate the square root by squaring both sides of the equation.
[tex]\[ (\sqrt{x + 4})^2 = (x + 1)^2 \][/tex]
[tex]\[ x + 4 = x^2 + 2x + 1 \][/tex]
Next, rearrange the terms to bring all of them to one side of the equation.
[tex]\[ x + 4 - x^2 - 2x - 1 = 0 \][/tex]
Then, combine like terms.
[tex]\[ -x^2 - x + 3 = 0 \][/tex]
Or equivalently,
[tex]\[ x^2 + x - 3 = 0 \][/tex]
This equation is a polynomial equation of degree 2, as the highest power of [tex]\(x\)[/tex] is 2. It fits the form [tex]\(ax^2 + bx + c = 0\)[/tex].
Therefore, [tex]\(\sqrt{x + 4} = x + 1\)[/tex] is a quadratic equation.
### Conclusion:
- Option (a) [tex]\(x^3 - x = x^2 + 2\)[/tex] is not a quadratic equation.
- Option (b) [tex]\(\sqrt{x + 4} = x + 1\)[/tex] is a quadratic equation.
Let's look at each option one by one.
### Option (a): [tex]\(x^3 - x = x^2 + 2\)[/tex]
To begin, we'll rearrange the terms to bring all terms to one side of the equation.
[tex]\[ x^3 - x - x^2 - 2 = 0 \][/tex]
Next, we combine like terms.
[tex]\[ x^3 - x^2 - x - 2 = 0 \][/tex]
The resulting equation is [tex]\(x^3 - x^2 - x - 2 = 0\)[/tex]. This equation is a polynomial equation of degree 3 (cubic), as the highest power of [tex]\(x\)[/tex] is 3. A quadratic equation must have a highest power of [tex]\(x\)[/tex] equal to 2.
Therefore, [tex]\(x^3 - x = x^2 + 2\)[/tex] is not a quadratic equation.
### Option (b): [tex]\(\sqrt{x + 4} = x + 1\)[/tex]
First, let's eliminate the square root by squaring both sides of the equation.
[tex]\[ (\sqrt{x + 4})^2 = (x + 1)^2 \][/tex]
[tex]\[ x + 4 = x^2 + 2x + 1 \][/tex]
Next, rearrange the terms to bring all of them to one side of the equation.
[tex]\[ x + 4 - x^2 - 2x - 1 = 0 \][/tex]
Then, combine like terms.
[tex]\[ -x^2 - x + 3 = 0 \][/tex]
Or equivalently,
[tex]\[ x^2 + x - 3 = 0 \][/tex]
This equation is a polynomial equation of degree 2, as the highest power of [tex]\(x\)[/tex] is 2. It fits the form [tex]\(ax^2 + bx + c = 0\)[/tex].
Therefore, [tex]\(\sqrt{x + 4} = x + 1\)[/tex] is a quadratic equation.
### Conclusion:
- Option (a) [tex]\(x^3 - x = x^2 + 2\)[/tex] is not a quadratic equation.
- Option (b) [tex]\(\sqrt{x + 4} = x + 1\)[/tex] is a quadratic equation.
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.